International Trends in the Field of Forensic Science Standardization, Forensic Science Standardization in Europe, Experience of Bosnia and Herzegovina - L. Trišić (Теория и практика судебной экспертизы)
The subject of this work is to present forensic science standardization trends in the world and in Europe with special review of the application of ISO/IEC 17025:2005 standard, which is a condition for forensic laboratory accreditation. Through the analysis of needs and constant efforts to make the forensic area simpler for cooperation and more practical for use, as well as to improve the quality of forensic analysis results and their acceptance beyond the borders of a country, the author will try to point out the significance of implementing this international standard, in terms of economics and cost-effectiveness, as well as overall rationality. Accepting and exchanging the best professional and scientific experiences, professional help and cooperation in the form of international exchange of forensic data bases, and unreserved acceptance of valid forensic laboratory results ensure the quality the forensic science and profession are striving for, as shown in the EU document titled “Creating a common European space for the forensic sciences 2020”. We believe that forensic activity standardization in Bosnia and Herzegovina will help in fighting terrorism and organized crime more effectively. In other words, the process of forensic analysis will be more valid and practical, forensic laboratories more competent, and court proceedings more effective through norming the forensic handling of evidence. Thus an important obligation of Bosnia and Herzegovina on its way to European integration will be fulfilled, because once a forensic laboratory receives an affirmation for its results, it becomes a benchmark for forensic analyses and crime detection.